2006
DOI: 10.1111/j.1471-4159.2006.04312.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of peroxynitrite in secondary oxidative damage after spinal cord injury

Abstract: Peroxynitrite (PON, ONOO ) ), formed by nitric oxide synthasegenerated nitric oxide radical ( AE NO) and superoxide radical (O 2 AE) ), is a crucial player in post-traumatic oxidative damage. In the present study, we determined the spatial and temporal characteristics of PON-derived oxidative damage after a moderate contusion injury in rats. Our results showed that 3-nitrotyrosine (3-NT), a specific marker for PON, rapidly accumulated at early time points (1 and 3 h) and a significant increase compared with sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
160
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 192 publications
(173 citation statements)
references
References 68 publications
7
160
2
4
Order By: Relevance
“…The current results, as well as those of earlier studies (Bao et al, 2003; Genovese et al, 2007; Liu et al, 2005; Scott et al, 1999; Scott et al, 2003; Scott et al, 2005; Xiong et al, 2007; Xiong and Hall, 2009), suggest that the administration of antioxidants that target PN or PN-derived radicals within the first hours after SCI should provide effective neuroprotection. In agreement with this idea, compounds that can either scavenge peroxynitrite such as uric acid (Scott et al, 2005) or FeTSPP (Genovese et al, 2007), or its derived free radicals such as tempol (Hillard et al, 2004; Xiong and Hall, 2009) have been reported to attenuate post-SCI spinal tissue damage.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The current results, as well as those of earlier studies (Bao et al, 2003; Genovese et al, 2007; Liu et al, 2005; Scott et al, 1999; Scott et al, 2003; Scott et al, 2005; Xiong et al, 2007; Xiong and Hall, 2009), suggest that the administration of antioxidants that target PN or PN-derived radicals within the first hours after SCI should provide effective neuroprotection. In agreement with this idea, compounds that can either scavenge peroxynitrite such as uric acid (Scott et al, 2005) or FeTSPP (Genovese et al, 2007), or its derived free radicals such as tempol (Hillard et al, 2004; Xiong and Hall, 2009) have been reported to attenuate post-SCI spinal tissue damage.…”
Section: Discussionsupporting
confidence: 73%
“…Prior studies in other laboratories (Liu et al, 2000; Scott et al, 1999) and our own (Xiong et al, 2007) have demonstrated 3-NT immunostaining in the injured spinal cord. Furthermore, recent work in our laboratory has provided convincing evidence for an important role of PN in the oxidative damage that occurs in the injured spinal cord and its relationship to other secondary injury events including intracellular calcium overload, mitochondrial dysfunction, and calpain-mediated cytoskeletal protein degradation (Xiong et al, 2007).…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations